Exploring the Photocatalytic Efficiency of Gold Nanoparticles Deposited on Ni-Al-Zr-Layered Double Hydroxides for Selective Glucose Oxidation - Nihel Dib; Frédéric Sauvage; Lucie Quéhon; Khadidja Khaldi; Sumeya Bedrane; José Juan Calvino; Redouane Bachir; Ginesa Blanco; Gwladys Pourceau (Molecules)
Confronting escalating challenges in energy security and environmental sustainability has intensified interest in renewable sources for fuels and chemicals. Among the most promising alternatives, sugars derived from biomass are emerging as a cornerstone in advancing an environmentally sustainable economy. Within this framework, the development of sunlight-driven carbohydrate oxidation is of significant interest, as it enables the production of a broad spectrum of high-value, bio-sourced chemicals through eco-friendly processes. Gold nanoparticles (Au NPs) immobilized on inorganic supports have demonstrated considerable potential in this area, although the methodology still requires further exploration. In this study, we explored the selective oxidation of glucose into the corresponding gluconic acid salt in presence of a novel Au/Ni-Al-Zr-layered double hydroxide (LDH) photocatalyst under standardized A.M. 1.5 G light illumination. To optimize the photocatalytic conditions, an experimental plan is herein proposed, highlighting the critical influences of both catalyst loading and pH. In optimal conditions, the Au catalyst demonstrated a high efficiency, achieving 87% glucose conversion and 100% selectivity towards gluconic acid in only 90 min. By means of long-pass filters to select the incident light energy to the photocatalytic reactor, we evidenced that the charge transfer processes were occurring from the Ni-Al-Zr LDH support to the gold nanoparticles, thus opening new directions towards further photocatalyst modifications. This work underlines the potential of Au/LDH materials for sunlight-driven photocatalysis and provides a pathway for the sustainable production of high-value chemicals from renewable biomass sources.